Linking Organizational Justice to Organizational Commitment Among Nigerian Police Officers - Sun, Ivan Y. (Criminal justice and behavior, 2022)
Organizational commitment is an imperative aspect of occupational attitudes as it signals employees’ willingness to stay with their organization and effectively achieve collective goals. Although recent studies have assessed factors influencing police officers’ organizational commitment, very little is known about the antecedents of police commitment in African countries. Based on a survey of Nigerian police officers, the study assesses the linkage between organizational justice and organizational commitment directly and indirectly through organizational trust and job satisfaction. Structural equation modeling (SEM) indicates that the relationship between organizational justice and organizational commitment is principally indirect through the mediating mechanisms of supervisory trustworthiness and job satisfaction. Officers who express greater organizational justice report higher trust in their management and supervisors and, subsequently, stronger job satisfaction, leading to higher organizational commitment. Implications for future research and policy are discussed.